ANALISIS PERFORMANSI SISTEM SELULER CDMA 2000 1X BERDASARKAN KEY PERFORMANCE INDIKATOR (KPI) - ., Dedi (Faculty of Engineering, Universitas Tanjungpura, 2013)
In this final measurement and analysis of network performance parameters based KPI (Key Performance Indicators) such as the Power Receive of MS (RxLevel), MS Transmit Power (Tx Power), Forward Frame Error Rate (FFER), Signal Strong (Ec / Io), Drop Call Rate and Call Setup Success Rate. From the analysis of test performance based on KPI parameters can be seen that the performance of the BTS Kota Baru and BTS Purnama still below ideal standards set by the company for parameter CSSR ( 97%), respectively 95.63% and 95.95%. As for the parameters to meet the standard KPI (0-2%) DCR respectively 0.26% and 0.27%. Quality calls for CSSR during test drive is also bad (still below the standard KPI) by 85%. DCR is still below the standard of 5%. In the area close to the BTS (2 km) all successful calls with an average RxLevel still normal between 69% -95%, Ec / Io normal by 7-8 dB, TxPo normal 23 dBm, and FFER 0-5% . While the area is far from BTS ( 2 km) most experienced call drop calls and blocked calls with an average RxLevel no longer normal between 95%, Ec / Io no longer normal 9 dB, TxPo no longer normal 23 dBm, and FFER 5%. This is what causes the fall in performance CSSR and DCR. The better the RF parameters of the BTS, the less likely it will drop the call and blocked calls. The smaller the drop the call and blocked call quality performance CSSR and DCR will increase (KPI standards). That is, the RF parameters and performance parameters are closely related. To achieve an ideal performance, both performance it must meet the standards of corporate ideal. Efforts that can be done such that the orientation of the antenna sector, then the addition of a repeater to increase coverage power that can be reached, the addition of modules to increase the capacity of CEMA BTS, or the addition of new base stations when the area was still solid drop call and blocked calls. Keywords: Keys Performance Indicator (KPI), Drive Test, CDMA 2000 1x